2016
DOI: 10.5307/jbe.2016.41.4.342
|View full text |Cite
|
Sign up to set email alerts
|

Modeling for Drying of Thin Layer of Native Cassava Starch in Tray Dryer

Abstract: Purpose:The drying of a thin layer of native cassava starch in a tray dryer was modeled to establish an equation for predicting the drying behavior under given conditions. Methods: Drying tests were performed using samples of native cassava starch over a temperature range of 40-60°C. We investigated the variation in the drying time, dynamic equilibrium moisture content, drying rate period, critical moisture content, and effective diffusivity of the starch with temperature. The starch diffusion coefficient and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
2
5
2
Order By: Relevance
“…By taking the average value of the R 2 and RMSE of each model, the Page model was determined to be the most suitable model to describe the drying behavior of cassava starch using a solar tray dryer, followed by the Midilli and Modified Page models. This differs from the thin-layer models of cassava pulp drying using an oven dryer by Charmongkolpradit and Luampon (2017) and a tray dryer by Aviara and Igbeka (2016), who found that the Midilli model and the Modified Hii et al model were the most accurate, respectively. These differences may be attributed to the different drying conditions.…”
Section: Model Simulationcontrasting
confidence: 74%
See 1 more Smart Citation
“…By taking the average value of the R 2 and RMSE of each model, the Page model was determined to be the most suitable model to describe the drying behavior of cassava starch using a solar tray dryer, followed by the Midilli and Modified Page models. This differs from the thin-layer models of cassava pulp drying using an oven dryer by Charmongkolpradit and Luampon (2017) and a tray dryer by Aviara and Igbeka (2016), who found that the Midilli model and the Modified Hii et al model were the most accurate, respectively. These differences may be attributed to the different drying conditions.…”
Section: Model Simulationcontrasting
confidence: 74%
“…The values of the intercept (ln(D o )) and slope (E a /R) were −21.925 and −1844.46, resulting in D o and E a being estimated as 3•× 10 −10 m 2 /s and 15.3 kJ/mole, respectively. The activation energy was lower than that observed by other researchers, including Aviara and Igbeka (2016) in their work regarding cassava starch drying in a tray dryer (32.933 kJ/mole) and Shen et al (2011) in their work regarding sorghum stalk drying using an oven dryer (21.4 kJ/mole).…”
Section: Model Simulationcontrasting
confidence: 68%
“…Table 4 shows the value of effective diffusivity at different drying temperatures. The effective diffusivity values in this experiment are found to be within a range of 10 − 11 to 10 − 9 m 2 /s, which is generally considered the acceptable range for most agricultural and food products (Aviara et al 2016). Another study, performed by Phitakwinai et al (2019), reports that the effective diffusivity values of coffee beans dried at 50°C-70°C ranged from 7.7544.10 − 10 to 1.4525.10 − 9 .…”
Section: Mathematical Modelingsupporting
confidence: 57%
“…This is because the water molecules are loosely bind to the lime matrix, which, in turn, makes evaporation easier [59]. The values of effective diffusivity in this experiment are within 10 À11 to 10 À9 m 2 /s, an acceptable range for agricultural and food products [60].…”
Section: Mathematical Modelingmentioning
confidence: 69%
“…The activation energy value in this experiment are in the range of generally acceptable value of activation energy for most food products, which is 14.42-43.26 kJ/mol [19]. Several studies have calculated the activation energy during the drying process, such as Aviara and Igbeka [60] in their work regarding modelling of cassava starch in a tray dryer (32.993 kJ/mol), Zhang et al [61] in their work regarding thin-layer modelling of apricot (16.5 kJ/mol), and Shen et al [36] in their work regarding thin-layer drying of sweet sorghum stalk (21.4 kJ/mol). It can be seen that the activation energy value in this experiment is higher compared to those studies, which may be influenced by several factors such as dryer design, operating temperature, and initial moisture content of the food products [36,55].…”
Section: Mathematical Modelingmentioning
confidence: 69%